Acoustic feedback cancellation in digital hearing aids: A sparse adaptive filtering approach. (July 2017) - Pradhan, Somanath; Patel, Vinal; Patel, Kashyap; Maheshwari, Jyoti; George, Nithin V.
Highlights: A new sparse adaptive feedback cancellation mechanism is developed. Employs the principle of zero attraction. Adaptive decorrelation filter is employed to improve convergence. Decorrelation filter is also updated online. Provides improved feedback cancellation for real life signals. Abstract: Cancelling the effect of acoustic feedback is a challenging task in the design of a behind the ear digital hearing aid. In traditional behind the ear digital hearing aids, feedback cancellation is usually achieved using an adaptive finite impulse response filter, the weights of which are updated using a suitable learning rule. However, the impulse response of the acoustic feedback path in a hearing aid is sparse in nature and traditional feedback cancellation systems are not designed to utilize this sparseness. An adaptive feedback canceller, which is trained using a set of sparse adaptive algorithms is designed in this paper to take advantage of the sparseness. Further, an attempt has been made to enhance the convergence of the feedback cancellation mechanism by introducing an adaptive de-correlation filter as well as using the concept of probe noise injection. The proposed feedback cancellation schemes are shown to provide improved and accurate feedback cancellation over traditional feedback cancellation mechanisms.